University of Florida Potato Variety Spot Light: Red LaSoda - Chad M. Hutchinson; Doug Gergela; David Dinkins; Edsel Redden (EDIS)
Revised! HS1078, a 5-page illustrated fact sheet by Chad M. Hutchinson, Doug Gergela, David Dinkins, and Edsel Redden, provides key details of this red-skinned fresh market variety of potato and includes production statistics from the UF/IFAS research and demonstration farm in Hastings FL. Published by the UF Department of Horticultural Sciences, December 2009.